A concise review of non-alcoholic fatty liver disease. Issue 1 (March 2015) - Than, Nwe Ni; Newsome, Philip N.
Abstract: Non-alcoholic fatty liver disease (NAFLD) is the hepatic manifestation of the metabolic syndrome and the incidence of which is rising rapidly due to the increasing epidemic of obesity in both adults and children. The initial accumulation of fat followed by subsequent inflammation is central to the development of liver damage, and is critically influenced by host factors including age, gender, presence of diabetes, genetic polymorphisms and more recently by the gut microbiome. An increasing body of data suggest that NAFLD is also an independent risk factor of cardiovascular disease, which remains the commonest cause of mortality in such patients. This review focusses on the pathogenesis of NAFLD, and the evolution of new approaches to the management and treatment of NAFLD. Highlights: NAFLD is an independent risk factor for cardiovascular disease irrespective of other metabolic risk factors. The mechanism behind the progression from simple steatosis to steatohepatitis in NAFLD was not fully understood. Insulin resistance, accumulation of triglycerides and free fatty acids play an essential role in the pathogenesis of NAFLD. New drugs are emerging to improve steatohepatitis and fibrosis in NAFLD.